Legal Reconstruction of Indonesian Sports Law: A Framework for Legal Protection and Certainty for Professional Athletes - Wide Putra Ananda; Siti Rodiah; Utari Dewi Fatimah (PT. Global Research Collaboration, 2026)
Purpose: This study examines the inadequacy of the Indonesian sports law system in providing legal protection and legal certainty for athletes and aims to formulate a reconstructed legal framework that recognizes athletes as professional legal subjects. Design/method/approach: This research employs a normative legal method based on doctrinal analysis, utilizing statutory, conceptual, comparative, and historical approaches. The study analyzes relevant legislation, jurisprudence, legal doctrines, and comparative legal systems, particularly in jurisdictions that formally recognize athletes as professionals. Findings: The study finds that Indonesian sports law remains predominantly administrative and fails to establish a rights-based framework for athletes. The absence of formal legal recognition creates a legal vacuum, weakening athletes’ contractual position, dispute resolution access, and social protection. The research proposes the enactment of an Athlete Profession Law, the institutional strengthening of the Indonesian Sports Arbitration Board (BAKI) with executorial authority, and the harmonization of national law with international lex sportiva principles. Research implications/limitations: As a normative legal study, the findings are derived from doctrinal analysis rather than empirical investigation. Future research is recommended to incorporate empirical data on athlete welfare, dispute cases, and policy implementation to strengthen the practical applicability of the proposed legal reforms. Originality/value: This study contributes to the development of sports law theory in Indonesia by introducing a rights-based reconstruction model grounded in Pancasila values and lex sportiva. It advances the concept of athletes as professional legal subjects and offers a comprehensive framework integrating legal recognition, protection, and institutional reform.